2019
DOI: 10.1155/2019/6519213
|View full text |Cite
|
Sign up to set email alerts
|

Study on Roof‐Coal Caving Characteristics with Complicated Structure by Fully Mechanized Caving Mining

Abstract: With mining technology and mechanization degree being improving, fully mechanized caving mining technology (FCM) has become a main method for thick coal seam extraction in China. However, roof-coal caving characteristics in turn restrict its recovery efficiency, especially for the coal seam with complicated structure (CCS), that is, the coal seam comprises hard or soft coal and gangue. In order to explore the key factors influencing the roof-coal caving and recovery characteristics, related research work has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…As mentioned in the introduction, carrying out mining processes in intact rock mass causes its imbalance [30,31] which affects excavation and the support system protecting it. This impact may have a different character and be the result of various phenomena occurring in the rock mass [5,[32][33][34][35][36]. A list of these phenomena and their effects on the support is shown in Figure 2.…”
Section: Phenomena Occurring In the Exploited Rock Mass And Their Effmentioning
confidence: 99%
“…As mentioned in the introduction, carrying out mining processes in intact rock mass causes its imbalance [30,31] which affects excavation and the support system protecting it. This impact may have a different character and be the result of various phenomena occurring in the rock mass [5,[32][33][34][35][36]. A list of these phenomena and their effects on the support is shown in Figure 2.…”
Section: Phenomena Occurring In the Exploited Rock Mass And Their Effmentioning
confidence: 99%
“…The study showed that as the weighted average particle size of the top coal increased, the volume of DB increased linearly and the maximum width of it increased non-linearly; as the weighted average particle size of the top coal increased, the top coal recovery ratio tended to increase and then decreased; high recoveries were achieved when the weighted average particle size of the top coal was in the range of 150-250 mm; and a relatively dispersed top coal particle size distribution and large standard deviations [13] were more favorable for the drawing of the top coal. Liang et al [14] studied the drawing characteristics of complex top coal, and believed that the cutting-caving ratio had an important influence on the drawing of the top coal. In the absence of manual intervention to break the coal, a cutting-caving ratio of 3 was most favorable for the drawing of the top coal.…”
Section: Introductionmentioning
confidence: 99%
“…This particularly applies to mining roof supports [1][2][3][4][5][6][7][8]. Their primary task is to protect mining excavations against deformation caused by the rock mass [1][2][3][4][5][6][7][8][9][10]. Therefore, in order to protect mine workings, various types of mining roof support are used [1][2][3]11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the hydraulic system and its control system are of particular importance due to the efficiency of the operation process itself, and the possibility of impact on the operating parameters of the section and the support. In this respect, hydraulic legs fulfil are executive elements that largely determine the effectiveness of the entire support being exposed to static and dynamic loads [6,7,20,21].…”
Section: Introductionmentioning
confidence: 99%